Komik "Lika-liku Perdagangan Orang" sebagai Media Sosialisasi Pencegahan Human Trafficking - Made Fitri Maya Padmi; Dewi Maria Herawati (PRoMEDIA, 2018)
Indonesia was one of the countries of origin, destination, and transit for men, women, and children to be victims of force labour and sex trafficking. Goverment of Indonesia worked along with international organization, IOM, did preventive actions in order to supress the number of human trafficking. These preventive actions included the publishing of comic book about human trafficking tittled “Lika-Liku Perdagangan Orang”. This paper would like to analyze the role of this comic book as a socialization and education media for increasing the social awareness of the danger of human trafficking. The research method used in this paper was qualitative research in which the researchers conducted libary research and in depth interview toward one of government body for migran workers, BNP2TKI and IOM. Concepts used in this paper were human trafficking and comic. The result of this research was the existance of this comic book added more medium and also helped the society to be more aware of the human trafficking case.Keywords: human trafficking, comic, socialization